1984
DOI: 10.1037/0022-3514.47.3.646
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and social interactional characteristics of ego identity statuses in college males.

Abstract: The development of ego identity is proposed to be a condition of cognitive factors expressed in, and reciprocally modified by, different styles of social interaction. Among 99 young adult men, identity statuses were determined by interview (Marcia, 1966); cognitive complexity was assessed by means of Schroder, Driver, and Streufert's (1967) Paragraph Completion Test; and social interactional styles were determined via a Bales (1951) interaction process analysis of small group discussions of moral dilemma (Rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 27 publications
0
35
0
1
Order By: Relevance
“…We have suggested that the identity deficit is developmentally caused whereas tbe identity conflict is not If tbat is correct, then identity deficits should occur mainly among adolescents and at midlife Identity conflicts may occur at any time Alternatively, it is plausible tbat identity conflicts would occur most when someone has recently made commitments and is trying to fulfill them, for it may be then that one discoyers tbe conflicts with other commitments If so, identity conflict crises may be most likely to occur in the postadolescent, young adult penod(s) (cf Leyinson et al , 1978, also Beit-Hallahmi, 1977, Roeske & Lake, 1977 Tbe hypothesis of gender differences in crisis type at adolescence deseryes further study It is plausible that adolescent females may tend to haye identity conflicts whereas adolescent males may be prone to identity deficits (cf Gmsburg & Orlofsky, 1981) This may be either because females are less likely than males to repudiate parental influences (Bios, 1962), or because current social developments have posed particular identity dilemmas for women (Whitbourne & Waterman, 1979) such as role conflicts A last developmental issue is tbe relation between adolescent and mid-life identity deficit crises In Enkson's yiew (echoed by Leyinson et al , 1978), a failure to resolye a developmental task at the appropnate age creates further problems later on By applying tbat approach to identity development, one could plausibly argue that a failure to have a proper identity crisis at adolescence might increase the likelihood of mid-life crisis The opposite prediction is also plausible, however Certain lndiyiduals may be especially prone to introspect and to question themselves, whereas others may habitually deny or rationalize potential challenges to their belief structures (cf Slugowski et al , 1984) If stable dispositions do account for differences in proneness to identity crises, then people who have adolescent identity deficits may be more (not less) likely to experience mid-life crises…”
Section: Implications For Future Researchmentioning
confidence: 95%
“…We have suggested that the identity deficit is developmentally caused whereas tbe identity conflict is not If tbat is correct, then identity deficits should occur mainly among adolescents and at midlife Identity conflicts may occur at any time Alternatively, it is plausible tbat identity conflicts would occur most when someone has recently made commitments and is trying to fulfill them, for it may be then that one discoyers tbe conflicts with other commitments If so, identity conflict crises may be most likely to occur in the postadolescent, young adult penod(s) (cf Leyinson et al , 1978, also Beit-Hallahmi, 1977, Roeske & Lake, 1977 Tbe hypothesis of gender differences in crisis type at adolescence deseryes further study It is plausible that adolescent females may tend to haye identity conflicts whereas adolescent males may be prone to identity deficits (cf Gmsburg & Orlofsky, 1981) This may be either because females are less likely than males to repudiate parental influences (Bios, 1962), or because current social developments have posed particular identity dilemmas for women (Whitbourne & Waterman, 1979) such as role conflicts A last developmental issue is tbe relation between adolescent and mid-life identity deficit crises In Enkson's yiew (echoed by Leyinson et al , 1978), a failure to resolye a developmental task at the appropnate age creates further problems later on By applying tbat approach to identity development, one could plausibly argue that a failure to have a proper identity crisis at adolescence might increase the likelihood of mid-life crisis The opposite prediction is also plausible, however Certain lndiyiduals may be especially prone to introspect and to question themselves, whereas others may habitually deny or rationalize potential challenges to their belief structures (cf Slugowski et al , 1984) If stable dispositions do account for differences in proneness to identity crises, then people who have adolescent identity deficits may be more (not less) likely to experience mid-life crises…”
Section: Implications For Future Researchmentioning
confidence: 95%
“…Although I have heard other identity researchers postulate that few late adolescents are normally categorized as having a diffuse identity status, my reading of the existing data is not consistent with that assertion. For example, in studies in which the participants' identity statuses were assessed by interviews, Marcia (1966) found that 24% (21 out of 86) of his participants were classified as identity diffuse, 21% (18 out of 86) were achieved; Marcia (1967) reported that 19% (14 out of 72) of his sample was identity diffuse, 21% (15 out of 72) was achieved; and Slugoski, Marcia, and Koopman (1984) found that 35% (35 out of 99) of 3rd-and 4th-year university students were diffuse, 19% (19 out of 99) were achieved. Studies using objective measures of identity status (e.g., Adams, 1999) report similar findings: for example, Berzonsky et al (1990) found that 22% (26 out of 118) of a sample of university students was identity diffuse and 26% (31 out of 118) was achieved; Berzonsky and Neimeyer (1994) found that 22% (37 out of 172) of their sample was identity diffuse, 32% (55 out of 172) was achieved.…”
Section: Identity Diffusionmentioning
confidence: 97%
“…With respect to those who have gone on to postsecondary education, this is somewhat remarkable given all of the disconfirming information to which they probably have been exposed. It is likely that these discomfiting communications either ''go in one ear and out the other'' or are actively resisted (Slugoski, Marcia, & Koopman, 1984). This foreclosed identity must then be defended against further disconfirmation during young adulthood, middle age, and old age.…”
Section: Foreclosurementioning
confidence: 98%